PENGARUH LIMBAH SERBUK BESI SEBAGAI PENGGANTI SEJUMLAH AGREGRAT HALUS TERHADAP CAMPURAN ASPAL - SAMSUL BAHRI; DWI AGUST SUSILO IRAWAN (Inersia: Jurnal Teknik Sipil, 2018)
The objective of this research examining  stability and flow value was to investigate the impact of the utility of iron fillings waste as a subtitute material for the number of suprisingly small aggregates in the mixture of asphalt. In this research, the portion of iron filings waste which given were 5 %, 10 % and 15 % of the heavy mixture smooth aggregates. The stability quantitative value was 2093 kg in 15 % iron filings contents. The higest flow quantitative value was 3,5  mm in 5 % iron filings contents. The result of characteristic validation Marshall on the number of subtituted smooth aggregates which used iron filings gave a standard coefficient specification BM.2005. So based on that, the iron fillings waste technically could be received as a subtitute material for the mixture of suprisingly small aggregates.